Angiographic severity does not correlate with fractional flow reserve in heavily calcified coronary arteries. Issue 2 (28th July 2016) - Johnson, Paul M.; Madamanchi, Chaitanya; Sharalaya, Zarina M.; Iqbal, Zahra; Gehi, Anil K.; Kaul, Prashant; Stouffer, George A.
Abstract : Objectives: To determine the relationship between severity of stenosis and hemodynamic significance in calcified coronary arteries. Background: Severity of stenosis is widely used to determine the need for revascularization but the effect of lesion calcification on hemodynamic significance is not well understood. Methods: Two hundred consecutive patients undergoing fractional flow reserve (FFR) testing of an intermediate coronary lesion with a pressure wire and intravenous infusion of adenosine were studied. Coronary calcium was quantified based upon radiopacities at the site of the stenosis on cineangiography using the method of Mintz et al. (0 = none or mild calcium, 1 = moderate calcium, 2 = severe calcium). Results: Mean age was 61 ± 11 years, 66% were males, 87.5% had hypertension, 44.5% had diabetes, and 20.5% were current smokers. The mean coronary stenosis by quantitative coronary angiography was 60 ± 12% and the mean FFR was 0.83 ± 0.08. There were 109, 45, and 46 patients classified as Calcium Score of 0, 1, or 2, respectively. Compared to those with no/mild or moderate calcification, patients with severe coronary calcium were older and more likely to have chronic kidney disease and pulmonary disease. The correlation between angiographic severity and FFR decreased as lesion calcification increased [calcium score = 0 ( R 2  = 0.25, P  < 0.005); calcium score = 1 ( R 2  = 0.11, P  < 0.005); calcium score = 2 ( R 2  = 0.02, P  = 0.35)]. Conclusions: In patients with heavily calcified coronary lesions, there was no association between angiographic stenosis and hemodynamic significance and FFR is needed to determine hemodynamic significance of intermediate lesions. © 2016 Wiley Periodicals, Inc.